Studi Implementasi Eco Friendly Architecture pada Trihita Alam Eco School Bali - Salshabila, Jasmine; Agustin, Dyan (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2025)
Environment-based education is an educational method that makes nature the centre of interactive and hands-on learning. This approach aims to make students more aware of the importance of understanding the condition and potential of nature which is an important part of human life that is always in contact with nature. Trihita Alam Eco School Bali is a school that emphasises a nature education approach or holistic education that aims not only to develop students' academic intelligence, but also to teach them to appreciate and care for the surrounding environment and strengthen their relationship with nature. This research aims to examine how the application of Eco Friendly Architecture at Trihita Alam Eco School Bali can reduce negative impacts on the environment. The research method used is qualitative method. Qualitative research methods can provide deep insights into the experiences, perceptions, and impacts of using sustainable architecture. The results of the study highlighted that this school promotes an environmentally friendly lifestyle, including in the infrastructure of the school building which is made from natural materials and is environmentally friendly. In conclusion, the application of Eco-Friendly Architecture at Trihita Alam Eco School Bali not only builds a healthy and comfortable learning environment for students, but actively contributes to environmental conservation and fosters environmental awareness among students, teaching staff, and the surrounding community.